Would a comprehensive hearing aid fitting process lead to placebo effects compared to a simple process? - Wu, Yu-Hsiang; Dorfler, Megan; Stangl, Elizabeth; Oleson, Jacob (Frontiers in Audiology and Otology, 2024)
Objectives Placebo effects refer to the impact of a treatment on health outcomes that cannot be attributed to the treatment itself. The current study aimed to investigate whether a comprehensive hearing aid fitting process would induce placebo effects compared to a simple process, and whether personal attributes such as personality traits could predict susceptibility to these effects. Design Thirty adults with hearing loss completed the study. The study began with a fitting session in which the field trial hearing aid configuration (the actual fitting) was set, followed by two experimental conditions. Each condition involved a fake hearing aid fitting and a 3-week field trial. In the fake fitting, bilateral hearing aids were fitted using the Comprehensive protocol (CM) that included multiple assessments and probe-microphone verification or the Streamlined protocol (ST) that did not involve any assessments other than a hearing test. The same hearing aid amplification settings established in the actual fitting, rather than the settings from the fake fittings, were used in the field trials for both conditions. Patient outcomes were measured using the International Outcome Inventory for Hearing Aids (IOI-HA), which was administered as both retrospective self-reports and ecological momentary assessment (EMA) surveys. Personality was assessed using the NEO Five-Factor Inventory. Upon completion of the study, participants expressed their hearing aid preferences based on hearing aids' real-world performances (prefer CM, prefer ST, or no preference). Results For both retrospective self-reports and EMA, the IOI-HA scores of the CM and ST conditions did not significantly differ. Among the 30 participants, 22 expressed a preference for either CM (n = 14) or ST (n = 8). Younger participants and those with higher levels of agreeableness were more likely to have a hearing aid preference. Conclusions At the group level, comprehensive hearing aid fitting process did not generate a placebo effect leading to better outcomes compared to a simple process. However, despite the absence of differences in hearing aid settings, most (73%) participants were affected by placebo effects, believing that one fitting process yielded better real-world outcomes than the other. Personal attributes including personality traits and age are associated with susceptibility to placebo effects.